Measles outbreak in Bosnia and Herzegovina in 2024: Can we trust numbers to predict the disease course and burden to the healthcare system? - Amila Muratspahić; Irma Dizdarević; Rusmir Baljic; Meliha Hadžović Čengić; Ahmed Velić; Velida Mulabdić (Journal of Global Antimicrobial Resistance)
AIM: To analyze the clinical features and laboratory parameters in patients suffering from measles during the outbreak in Bosnia and Herzegovina in 2024. BACKGROUND: Due to low vaccination coverage in Bosnia and Herzegovina, measles outbreaks occur every several years, particularly among unvaccinated children. METHODS: Retrospective observational study included 279 subjects diagnosed with measles and admitted to the Clinic of Infectious Diseases, Clinical Center University of Sarajevo, from February to July 2024. The data were obtained from patients' medical histories. Standard laboratory techniques were used to measure the levels of C-reactive protein (CRP), white blood cells, platelets, alanine aminotransferase, aspartate aminotransferase and lactate dehydrogenase. Statistical analysis was done using SPSS 20.0. Values of p<0.05 were considered statistically significant. RESULTS: Levels of observed laboratory parameters did not show statistically significant differences between patients who required longer hospital stays and utilization of healthcare system. The most frequent complications were dehydration, pneumonia and ear infections. Prior to hospital admission, before onset of rash, and bacterial superinfections, 28.6% of patients were prescribed with antibiotics. Those who experienced bacterial superinfections did not have statistically significant higher levels of CRP and white blood cells. The most serious complications were two cases of meningoencephalitis and one case of transversal myelitis. Fatal outcome was reported in two unvaccinated patients with previous comorbidites. CONCLUSIONS: Although measles is a vaccine-preventable disease, it still occurs in epidemic proportions in certain regions, leading to high utilization of healthcare system services. Routine laboratory findings cannot accurately predict the course and outcome of the disease.